Learning styles and academic achievement among building construction students - Mohamad, Mimi Mohaffyza (2013)
This study is conducted to identify how learning styles (LS) influence the students’ academic achievement based on cognitive mastery and vocational elements in Building Construction Subject (BCS) involving the students and teachers of Building Construction Course (BCC) from three secondary vocational schools in Johor. Descriptive case study was applied with quantitative and semi-structured interview as supporting components in this study. The quantitative data were gathered based on Felder and Silverman Learning Styles Model (FSLSM), Felder- Soloman Index of Learning Styles (ILS) and vocational cognitive elements which consist of the aspects of knowledge, skills and problem solving were taken into account in constructing the question items. Purposive sampling was used to select the schools and stratified sampling procedure was applied in the selection of 128 students as research respondents. Purposive sampling was also chosen to select teachers as respondents for interview. The quantitative data was analyzed in descriptive and inferential statistic involving parametric test; Chi Square and Multivariate Analysis of Variance (MANOVA). Kruskal-Wallis was used for nonparametric test for this study. The content analysis for interview was managed to analyze the narrative text from interview record. The study discovered that students in BCC tend to be visual learners. Visual learners represent the input dimension of FSLSM and the result showed there are significant differences between input dimension with skills and problem solving but not with knowledge. The discussions with teachers revealed that most teachers accommodate students learning styles with cognitive mastery by using visual approach to increase students’ academic achievement. Research findings suggested a few framework of learning styles with vocational elements in BCS and concluded the need for a framework based on the dominant students’ learning style through the cognitive mastery and vocational elements. In conclusion, the research proposed that the Cognitive Learning Styles Framework (C-LSF) could act as a guideline for teachers to facilitate students to learn more effectively and to boost the academic achievement in Building Construction Subject.